Rural development and entrepreneurship: the entrepreneurial potential of students of agricultural engineering of the University of Leon in Spain. - Campelo Rodríguez, María Piedad (Historia y Comunicación Social, 2014)
In the framework of two projects on entrepreneurial skills development in three degrees programmes in “Green Engineering” at the University of Leon, we study the social, professional, and entrepreneurial profiles of 72 students using two questionnaires with 29 items. The results are: (i) the majority work experience related to the degree, (ii) a preference for working as an employee of a large enterprise or self-employment as a future professional career, and (iii) the value of integrating specific training to develop entrepreneurial competence and positive acceptance of it.